Conflitos e resistências do povo Chiquitano da terra e aldeia Vila Nova Barbecho - Chue, Soilo Urupe (2023)
To understand the conflicts and resistance that take place in the Indigenous Land and Aldeia Vila Nova Barbecho, it is necessary to bring into account the context of the Chiquitano people in Brazil and Bolivia. The Chiquitano people are one of the 43 peoples existing in the State of Mato Grosso. The name Chiquitano comes from the Spanish "chiquitos" which means small. Name given by the Spanish when they arrived in the center of South America, they found people with short stature, the doors of the houses were also low. Identity and nationality changes depending on the country you live in. The borders between the two countries were imposed in accordance with invasions and treaties without consulting the original Chiquitano people, guardians of nature and borders. The Vila Nova Barbecho Indigenous Land and Village where this work was developed is located on the border of Brazil and Bolivia. In the municipality of Porto Esperidião, MT/Brazil, 110 km from the city, and 480 km from Cuiabá-MT. On the border of Brazil and Bolivia there are intense conflicts between the Chiquitano people, farmers and politicians from the region, as they deny the existence of the Chiquitanos from this region in Brazil, in an attempt to make them invisible and deny the rights guaranteed by the 1988 Federal Constitution, but the Chiquitanos continue resisting. Objective: To understand the existing conflicts with the Chiquitano indigenous people, as well as to visualize the lines of resistance adopted by the Chiquitanos of the Vila Nova Barbecho indigenous land, highlight their territorial confrontation, struggles and conquests, increasingly strengthening the resistance mechanisms, reinforcing cultural singularity , ethnic and social. Methodology: The methodology used was quantitative. Bibliographic reviews were carried out on indigenous conflicts and resistance at the federal level (theses, dissertations, course completion works, scientific articles, indigenous productions, etc.). Consultation in the library of the higher education institution, and on online platforms for scientific journals, as well as on online platforms for disseminating indigenous works. Semi-structured interviews were carried out with leaders from the Vila Nova Barbecho village, recorded and later transcribed. Observation diary records were used. Interviews carried out with 5 people. Person 01 midwife, person 02 young, person 03 Chief during the interview period, people 4 and 5 an elderly couple. After receiving the free and informed consent form. Results: all interviewees highlighted what it was like to live in the past with what I call previous joy, the joy of living freely in the sacred space where their ancestors always lived. The sad side of history was also highlighted, the pain and suffering faced after the arrival of invaders, and even today the struggle continues to rescue the right to land and territory. Final considerations: The Chiquitanos continued to live on both sides of the borders, despite being displaced according to the interests of the rulers who made treaties without considering those who were interested in the border, that is, the indigenous Chiquitano population. More than maps to know where the border is, Chiquitanos easily learn what “maps” or ways to survive on one or the other side of the border are and try to adapt to the adverse contexts to which they are subjected, minimizing conflicts. It made possible for Chiquitanos the possibility of Brazil expanding towards Chiquitania. But here I am to say that more important than knowing where the border is, it's knowing how to cross the border when appropriate and being able to adapt to one side of the border or the other. This study enables the production of written documents in the form of articles or other records that can be made in the future, by me or other militant researchers from the Vila Nova Barbecho village.